2014
DOI: 10.3233/ch-131711
|View full text |Cite
|
Sign up to set email alerts
|

Altitude training induced alterations in erythrocyte rheological properties: A controlled comparison study in rats

Abstract: Altitude training is frequently used by athletes to improve sea-level performance. However, the objective benefits of altitude training are controversial. This study aimed to investigate the possible alterations in hemorheological parameters in response to altitude training. Sprague Dawley rats, were divided into 6 groups: live low-train low (LLTL), live high-train high (LHTH), live high-train low (LHTL) and their controls live high and low (LHALC), live high (LHC), live low (LLC). LHC and LHTH groups were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Hemorheological properties can help evaluate the oxygen delivery and utilization capacity in various subjects, for different exercise methods and exercise intensities, and between sexes [ 23 , 36 , 37 , 38 ]. In particular, hemorheological properties, including erythrocyte deformability and aggregation, are very important parameters because they are related to the surrounding microcirculation tissue and facilitate the exchange of oxygen and carbon dioxide [ 22 ]. In their study related to hypoxia and hemorheological properties, Grau et al [ 39 ] investigated the impact of mild-to-severe hypoxia on human erythrocyte-nitric oxide synthase (NOS)-dependent nitric oxide production, protein S-nitrosylation, and deformability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemorheological properties can help evaluate the oxygen delivery and utilization capacity in various subjects, for different exercise methods and exercise intensities, and between sexes [ 23 , 36 , 37 , 38 ]. In particular, hemorheological properties, including erythrocyte deformability and aggregation, are very important parameters because they are related to the surrounding microcirculation tissue and facilitate the exchange of oxygen and carbon dioxide [ 22 ]. In their study related to hypoxia and hemorheological properties, Grau et al [ 39 ] investigated the impact of mild-to-severe hypoxia on human erythrocyte-nitric oxide synthase (NOS)-dependent nitric oxide production, protein S-nitrosylation, and deformability.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorheological properties such as erythrocyte deformability and aggregation affect the oxygen delivery capacity of active skeletal muscles [ 21 , 22 ]. The blood flow through capillaries, which are smaller in diameter than erythrocytes and microcirculation, is accompanied by erythrocyte deformability [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations of these blood factors are involved in hypoxia and altitude training. Most often, hypoxia or altitude conditions will result in increased RBC and HCT ( Bor-Kucukatay et al, 2014 ; Stokke et al, 1986 ). The present results from simulated altitude training reaffirm the view that a low oxygen environment boosts RBC and HCT.…”
Section: Discussionmentioning
confidence: 99%
“…This research group demonstrated a reduction in the volume and deformability of human erythrocytes induced by hypoxic exercise. Conversely, conflicting results come from studies performed on laboratory animals [16,17]. Effects of living and training at different altitudes on red blood cell deformability and erythrocyte aggregation were studied by Bor-Kucukatay et al in Sprague Dawley rats [16].…”
Section: Haemorheological Changes With Altitudementioning
confidence: 99%